Respuesta :
Answer:
[tex]\cos \left ( 225^{\circ} \right )\cos \left ( 75^{\circ} \right )=\frac{1-\sqrt{3}}{4}[/tex]
Step-by-step explanation:
To find: [tex]\cos \left ( 225^{\circ} \right )[/tex]
[tex]\cos \left ( 225^{\circ} \right )=\cos \left ( 180^{\circ}+45^{\circ} \right )[/tex]
Now, angle [tex]180^{\circ}+45^{\circ}[/tex] lies in third quadrant in which [tex]\cos[/tex] is negative
So, [tex]\cos \left ( 225^{\circ} \right )=\cos \left ( 180^{\circ}+45^{\circ} \right )=-\cos 45^{\circ}[/tex]
We know that [tex]\cos 45^{\circ}=\frac{1}{\sqrt{2}}[/tex]
So, [tex]\cos \left ( 225^{\circ} \right )=\frac{-1}{\sqrt{2}}[/tex]
To find: [tex]\cos \left ( 75^{\circ} \right )[/tex]
[tex]\cos \left ( 75^{\circ} \right )=\cos \left ( 90^{\circ}-15^{\circ} \right )[/tex]
We know that angle [tex]90^{\circ}-15^{\circ}[/tex] lies in first quadrant in which [tex]\cos[/tex] is positive. Also, [tex]\cos \left ( 90-\alpha \right )=\sin \alpha[/tex]
So, [tex]\cos \left ( 75^{\circ} \right )=\cos \left ( 90^{\circ}-15^{\circ} \right )=\sin \left ( 15^{\circ} \right )[/tex]
We will use formula: [tex]\sin \left ( A-B \right )=\sin A\cos B-\cos A\sin B[/tex]
Here,
[tex]\sin \left ( 15^{\circ} \right )=\sin \left ( 45^{\circ}-30^{\circ} \right )=\sin \left ( 45^{\circ} \right )\cos \left ( 30^{\circ} \right )-\cos \left ( 45^{\circ} \right )\sin \left ( 30^{\circ} \right )=\left ( \frac{1}{\sqrt{2}} \right )\left ( \frac{\sqrt{3}}{2} \right )-\left ( \frac{1}{\sqrt{2}} \right )\left ( \frac{1}{2} \right )=\frac{\sqrt{3}}{2\sqrt{2}}-\frac{1}{2\sqrt{2}}=\frac{\sqrt{3}-1}{2\sqrt{2}}[/tex]
Therefore,
[tex]\cos \left ( 225^{\circ} \right )\cos \left ( 75^{\circ} \right )=\left ( \frac{-1}{\sqrt{2}} \right )\frac{\sqrt{3}-1}{2\sqrt{2}}=\frac{1-\sqrt{3}}{4}[/tex]